(untitled) (Revista Científica Interdisciplinaria Investigación y Saberes, 2024)
It is crucial to provide a comprehensive support system that addresses both the medical aspects of treatment and the emotional and social needs of everyone involved. Therefore, the study focuses on identifying and addressing the patient’s beliefs and perceptions about medications and the underlying disease. Mixed research was used with a survey developed in Google Forms, along with analysis of results, to achieve a comprehensive understanding.The sample consisted of patients with chronic diseases aged 35 to 80 years. The results revealed that 88.3% of respondents recognized the importance of taking their medications as prescribed, highlighting a widespread understanding of treatment adherence. In summary, this study has been instrumental in understanding patients’ perceptions of medications in chronic diseases.